Towards gender-responsive transport planning: A case study of suburban passenger travel - Yurii Davidich; Andrii Galkin (Journal of Urban Mobility)
This research investigates the influence of gender on suburban passenger transport choices, aiming to enhance the efficiency and inclusivity of public transport systems. The study employs a two-stage data collection approach, encompassing surveys and operational data, to identify key criteria influencing mode choice for men and women. Statistical analysis reveals distinct gender-based preferences, with women prioritising comfort and safety, while men focus on travel time and cost. The research culminates in the development of mathematical models to predict the proportion of male and female passengers opting for specific transport modes, offering valuable insights for transport planners and policymakers. The findings underscore the necessity of integrating gender-specific considerations into transport planning and policy-making to create more equitable and efficient suburban transport systems, particularly in developing regions where gender disparities in transport access persist.